Mathematical Modeling of a Multilayered Drift-Stabilization Method for Micro-UAVs Using Inertial Navigation Unit Sensor - Hyeok-June Jeong; Myunggwon Hwang; Hanmin Jung; Young-guk Ha (Journal of Applied Mathematics)
This paper proposes a multilayered quadrotor control method that can move the quadrotor to the desired goal while resisting disturbance. The proposed control system is modular, convenient to design and verify, and easy to extend. It comprises three layers: a physical layer, a displacement control layer, and an attitude control layer. The displacement control layer considers the movement of the vehicle, while the attitude control layer controls its attitude. The physical layer deals with the physical operation of the vehicle. The two control layers use a mathematical method to provide minute step-by-step control. The proposed control system effectively combines the three layers to achieve drift stabilization.